AN ANALYSIS OF TEACHING METHODS USED BY ENGLISH TEACHERS AT SD NEGERI 22 KOTA BENGKULU - Violeta Aprili; Washlurachim Safitri; Ivan Achamd Nurcholis (Teaching English and Language Learning English Journal, 2025)
The purpose of this research is to analyze the teaching methods employed by English teachers at SD Negeri 22 Kota Bengkulu. The study applies a descriptive research design, utilizing observations conducted in six different classes. The results indicate that the Grammar Translation Method (GTM) is the predominant teaching approach in the school. Teachers frequently use explicit grammar instruction, translation exercises, and vocabulary memorization to facilitate language learning. Although this method effectively reinforces grammatical accuracy, it lacks interactive elements that promote fluency. The study suggests incorporating more communicative teaching strategies, such as Communicative Language Teaching (CLT) and the Direct Method, to enhance students' engagement and practical language use. Keywords: Teaching Methods, Grammar Translation Method, Primary Education, SD Negeri 22 Kota Bengkulu